A STUDY OF INFORMAL CREDIT SERVICES AVAILABLE TO RICE FARMERS IN SAINT BERNARD, SOUTHERN LEYTE - Armenia, Pedro T. (Annals of Tropical Research, 1989)
The study revealed that cash and credit in-kind were extended by the informal lenders to many rice and non-rice farmers. The informal lenders employed two major credit arrangements, namely: the butang and plete systems. The butang system requires borrowers to pay one cavan of palay for every cash credit which averaged P74 and payable within 4 months. One variant of the butang scheme is the practice where borrowers pay 2.4 cavans of palay for an average credit worth P204 of fertilizer and pesticides which is payable within 3 months. In the plete credit scheme, the borrowers either pay an average of 2.6 cavans of palay as interest for the P1,000 cash loan payable within 5 months or an average monthly interest of 12.5%. In the butang credit arrangement, all types of lenders generally collected more than the total credit to farmers although none of them collected 100% of the total amount due. Under the plete system, the lenders generally could not collect the total interest due during the period covered by the study.